Effects of three months of detraining on the health profile of older women after a multicomponent exercise program - Leitão, Luís (2019)
Physical exercise results in very important benefits including preventing disease and promoting the quality of life of older individuals. Common interruptions and training cessation are associated with the loss of total health profile, and specifically cardiorespiratory fitness. Would detraining (DT) promote different effects in the cardiorespiratory and health profiles of trained and sedentary older women? Forty-seven older women were divided into an experimental group (EG) and a control group (CG) (EG: n = 28, 70.3 ± 2.3 years; CG: n = 19, 70.1 ± 5.6 years). Oxygen uptake (VO2) and health profile assessments were conducted after the exercise program and after three months of detraining. The EG followed a nine-month multicomponent exercise program before a three-month detraining period. The CG maintained their normal activities. Repeated measures ANOVA showed significant increases in total heath and VO2 (p < 0.01) profile over a nine-month exercise period in the EG and no significant increases in the CG. DT led to greater negative effects on total cholesterol (4.35%, p < 0.01), triglycerides (3.89%, p < 0.01), glucose (4.96%, p < 0.01), resting heart rate (5.15%, p < 0.01), systolic blood pressure (4.13%, p < 0.01), diastolic blood pressure (3.38%, p < 0.01), the six-minute walk test (7.57%, p < 0.01), Pulmonary Ventilation (VE) (10.16%, p < 0.01), the Respiratory Exchange Ratio (RER) (9.78, p < 0.05), and VO2/heart rate (HR) (16.08%, p < 0.01) in the EG. DT may induce greater declines in total health profile and in VO2, mediated, in part, by the effectiveness of multicomponent training particularly developed for older women.